Hubungan penerimaan diri dan harga diri pada remaja dengan orangtua bercerai - Tika Pratiwi Andani (Fakultas Psikologi, 2020)
The role of parents is very important in the formation of self-esteem in dolescents. Losing one of their parents because divorce will inhibit the formation of self-esteem in adolescents. The purpose of this study is to determine whether there is a relationship between self-acceptance and self-esteem in adolescents with divorced parents. Sampling technique using purposive sampling with the number of subjects is 84 teenagers who have divorced parents. Data analysis technique using Pearson product moment analysis technique. The measuring tool used was using Powell's self-residence scale and RSES self-esteem scale (Rosenberg Self-Esteem Scale) scales from Rosenberg. The results showed a significant positive relationship between self-acceptance and self-esteem of adolescents with divorced parents. This shows that the higher the self-acceptance of adolescents with divorced parents will be the higher the self-esteem of adolescents.